FM19G11 reverses endothelial dysfunction in rat and human arteries through stimulation of the PI3K/Akt/eNOS pathway, independently of mTOR/HIF‐1α activation. (12th January 2015) - El Assar, M; Sánchez‐Puelles, J M; Royo, I; López‐Hernández, E; Sánchez‐Ferrer, A; Aceña, J L; Rodríguez‐Mañas, L; Angulo, J
<x xml:space="preserve">Abstract</x> Background and Purpose FM19G11 up‐regulates mammalian target of rapamycin (mTOR)/hypoxia inducible factor‐1α (HIF‐1α) and PI3K/Akt pathways, which are involved in endothelial function. We evaluated the effects of FM19G11 on defective endothelial vasodilatation in arteries from rats and humans and investigated the mechanisms involved. Experimental Approach Effects of chronic in vivo administration of FM19G11 on aortic endothelial vasodilatation were evaluated together with ex vivo treatment in aortic and mesenteric arteries from control and insulin‐resistant rats (IRR). Its effects on vasodilator responses of penile arteries (HPRAs) and corpus cavernosum (HCC) from men with vasculogenic erectile dysfunction (ED) (model of human endothelial dysfunction) were also evaluated. Vascular expression of phosphorylated‐endothelial NOS (p‐eNOS), phosphorylated‐Akt (p‐Akt) and HIF‐1α was determined by immunodetection and cGMP by elisa. Key Results Chronic administration of FM19G11 reversed the impaired endothelial vasodilatation in IRR. Ex vivo treatment with FM19G11 also significantly improved endothelium‐dependent vasodilatation in aorta and mesenteric arteries from IRR. These effects were accompanied by the restoration of p‐eNOS and cGMP levels in IRR aorta and were prevented by either NOS or PI3K inhibition. p‐Akt and p‐eNOS contents were increased by FM19G11 in aortic endothelium of IRR. FM19G11‐induced restoration of endothelial vasodilatation was unaffected by mTOR/HIF‐1α inhibitors. FM19G11 also restored endothelial vasodilatation in HPRA and HCC from ED patients. Conclusions and Implications Stimulation of the PI3K/Akt/eNOS pathway by FM19G11 alleviates impaired NO‐mediated endothelial vasodilatation in rat and human arteries independently of mTOR/HIF‐1α activation. This pharmacological strategy could be beneficial for managing pathological conditions associated with endothelial dysfunction, such as ED.